Leaves of the Same Tree Trade and Ethnicity in the Straits of Melaka - Andaya, Leonard Y. (University of Hawaii Press, 2008)
Despite the existence of about a thousand ethnolinguistic groups in Southeast Asia, very few historians of the region have engaged the complex issue of ethnicity. Leaves of the Same Tree takes on this concept and illustrates how historians can use it both as an analytical tool and as a subject of analysis to add further depth to our understanding of Southeast Asian pasts. Following a synthesis of some of the major issues in the complex world of ethnic theory, the author identifies two general principles of particular value for this study: the ideas that ethnic identity is an ongoing process and that the boundaries of a group undergo continual-if at times imperceptible-change based on perceived advantage. The Straits of Melaka for much of the past two millennia offers an ideal testing ground to better understand the process of ethnic formation.